Dynamic responses of Schwedler dome and geodesic dome to wind load - Radoń, Urszula; Szaniec, Waldemar; Pawlak, Urszula; Zabojszcza, Paweł (Archives of Civil Engineering, 2026)
The paper analyses the effect of wind load on the dynamic responses of two domes. This is not a standard design situation, therefore static analysis alone is not sufficient. The main objective of this paper is to compare the results obtained from the application of dynamic equilibrium equations and those obtained from static analysis. The authors wanted to determine the sensitivity of the domes to the wind load. Inertial forces and dynamic equilibrium equations were taken into account in the calculations. The integration of the equations of motion was performed using the unconditionally stable version of Newmark’s method. Numerical calculations were performed using the author’s MES3D program. Two patterns and two heights of single-layer steel domes were considered, i.e. a low Schwedler dome and a high geodesic dome. The structural stability and damping capacity of the domes were compared. The analysis includes a modal study to determine the natural frequencies and their corresponding vibration modes. Then, the displacements and accelerations of the keystone of both domes were assessed.
Keywords: modal analysis; wind load; Newmark method; Schwedler dome; geodesic domes